A link selection strategy for cooperative ad-hoc networks. (November 2015) - Annadurai, Chinnamuthu; Nagarajan, Velmurugan
Abstract: Cooperative ad-hoc networks are popular because of their ability to provide reliable communication. In this paper, we consider a cooperative ad-hoc network consisting of a source, two decode-and-forward relays and a destination. The source intends to transmit its data to the destination directly as well as through relays. We employ a weighted selection combining at the destination which chooses either the weighted source-to-relay1-to-relay2-to-destination link or source-to-destination link depending upon the instantaneous signal-to-noise-ratio. We derive the end-to-end symbol error probability (SEP) of a triple-hop cooperative network with binary phase-shift keying for a flat, slow Rayleigh fading channel. Further, we develop an algorithm which investigates the performance of this cooperative ad-hoc network in terms of SEP. Results show that the cooperation among the nodes and weighted selection combining improves the performance of ad-hoc networks when compared to a point-to-point link and conventional selection combining.